MANAJEMEN APLIKASI BIMBINGAN KONSELING BERBASIS WEB - hidayat, imam; Andi, Andi; Nugroho, Wahyu (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2024)
This study aims to develop and evaluate web-based guidance and counseling application management . This application is designed to facilitate the guidance and counseling process by providing easy and integrated access to students, teachers, and counselors. With using research methods​ Waterfall model software development approach . Development stages include needs analysis, application design, implementation, and testing. With existence testing The results of the study show that this application is effective in providing a platform that facilitates access to counseling guidance and facilitates communication between students and counselors. The use of this application also contributes to increasing student satisfaction with guidance and counseling services at school. This research is expected to be a reference for the development of similar applications in other schools, as well as contribute to the application of technology in the world of education